Development of E-Comic-Based Mathematics Teaching Materials on the Topic of Multiplication and Division with Realistic Mathematics Education (RME) Approach - Nurbaiti Widyasari; Anisa Nurcahyani (Kreano: Jurnal Matematika Kreatif-Inovatif, 2021)
The purpose of this study was to develop E-Comic-based mathematics teaching materials on the topic of multiplication and division with the Realistic Mathematics Education (RME) approach. This research is a research and development using the Hannafin and Peck development model. This model consists of three stages, namely needs assessment, design, development and implementation. The subjects in this study were students of class 3A SDN Pinang 2 Tangerang City. The results research obtained included 1) material expert validation got 95,38% with very valid criteria, 2) linguist validation got 87,5% with very valid criteria, 3) media expert validation got 97,5% with very valid criteria. Assessment of student responses 1) small group test got 95,41% with high criteria, 2) large group test got 99% with high criteria. Based on the results of the assessment, the E-Comic-based mathematics teaching materials developed are valid and can be used as additional teaching material for teaching the concept of multiplication and division.